Minecraft : combat handbook - Milton, Stephanie; Soares, Paul (Writer on computer games); Cordner, Theo; CNBMinecraft; FyreUK (New York, NY : Scholastic, 2014)
An official reference to Minecraft combat explains what players need to defend against hostile monsters and enemy players, covering subjects ranging from fort building and armor crafting to weapons and setting mob traps.
Keywords: Minecraft (Game) -- Handbooks, manuals, etc. -- Juvenile literature; Video games -- Handbooks, manuals, etc. -- Juvenile literature